METHODOLOGICAL AND PRACTICAL ASPECTS OF IDENTIFYING DEVELOPMENT POLES AND GROWTH POINTS IN THE REGIONAL ECONOMY - A. A. Urunov; A. M. Avezova; M. A. Nasimov (Вестник университета)
Criteria of allocation of development poles and growth points in the regional economy have been proved. Technique of allocation of potential development poles and growth points based on the account of multiplicative effect in vertically diversified enterprises has been developed. It has been revealed and quantitatively estimated that the higher attractiveness of the development poles in the regional economy is due to the synergetic effect, which is manifested in the diversification and modernization of production in the compactly located territory of the region. A map of poles and growth points in Sughd region of the Republic of Tajikistan has been compiled and it has been proved that a development pole has been formed in the region, located in the North of Khujand and in adjacent to it B. Gafurovsky and J. Rasulovsky districts. It is called the “North development pole” and is at the stage of maturity of the life cycle, as it fully characterizes the market relations that function in the development pole. The results of the study can be used in the development of investment rating and typology of the country’s regions, social policy and state regulation of spatial development.